Social relations and scholastic achievement: Insights from engineering students through a mixed method study - Syed Inshaallah Tahir; Tasleema Jan (Acta Psychologica)
The study was conducted on engineering students pursuing a B.Tech. in Civil and Mechanical engineering. The study involves a Mixed Method Design. A stratified sampling technique was used to collect the data from the sample subjects (Students), and for the qualitative part, thirty (30) teachers were purposively selected. The sample from Civil engineering students consists of 167 students, and 107 Mechanical engineering students selected randomly. The study compares the two groups in terms of Social Relations and Scholastic Achievement. The impact of Social Relations of students on their Scholastic Achievement was also studied. The opinions were pooled from the Teachers. Descriptive and inferential statistical analyses were conducted, including Mean, Standard Deviation, t-tests, Effect size (Cohen's d), linear regression and Thematic analysis. The findings reveal that Civil engineering students have higher Social Relations and better Scholastic Achievement than their Mechanical counterparts. Further, our results emphasize the significance of good social relationships in predicting the scholastic achievement of students. Therefore, the findings suggest that encouraging surroundings that promote healthy social interactions and connections among engineering students and their teachers and classmates ought to be a top priority for educators and other stakeholders.